تقويم كتاب الدِّراسات الاجتماعيّة للصف الأول المتوسط في ضوء معايير الجودة الشاملة من وجهة نظر معلِّمي الدِّراسات الاجتماعية - الدكتور محمد بن حارب الشريف (مجلة العلوم التربوية والنفسية, 2024)
This study aimed at evaluating the social studies textbook for the first intermediate grade according to the total quality standards form the viewpoints of social studies teachers in Dawadmi. The survey descriptive method was utilized. The sample comprised (84) male and female teachers. A questionnaire including the total quality management standards required for the social studies textbook for the first intermediate grade was prepared. It consisted of four dimensions: (quality of book production, goals, content, evaluation methods). Results showed that the availability level of the total quality standards within the social studies textbook for the first intermediate grade was high (mean= 3.99). Quality of book production was first ranked (mean= 4.04). It was followed by content quality (mean= 4), goal quality (mean= 2.97), and (evaluation quality), respectively. The study recommended the need to rehabilitate and train social studies teachers in light of the comprehensive quality approach and its standards, and to focus on ensuring that evaluation methods cover all levels of Bloom’s knowledge.